Meteorites and the RNA world: II. Synthesis of nucleobases in carbonaceous planetesimals and the role of initial volatile content - Paschek, Klaus; Semenov, Dmitry; Pearce, Ben K. D.; Lange, Kevin; Henning, Thomas; Pudritz, Ralph E. (Arxiv, 2022)
Prebiotic molecules, fundamental building blocks for the origin of life, have been found in carbonaceous chondrites. The exogenous delivery of these organic molecules onto the Hadean Earth could have sparked the polymerization of the first RNA molecules in Darwinian ponds during wet-dry cycles. Here, we investigate the formation of the RNA and DNA nucleobases adenine, uracil, cytosine, guanine, and thymine inside parent body planetesimals of carbonaceous chondrites. An up-to-date thermochemical equilibrium model coupled with a 1D thermodynamic planetesimal model is used to calculate the nucleobase concentrations. Different from the previous study (Pearce & Pudritz 2016), we assume initial volatile concentrations more appropriate for the formation zone of carbonaceous chondrite parent bodies. This represents more accurately cosmochemical findings that these bodies have formed inside the inner, ∼2−5au, warm region of the solar system. ...
Online veröffentlicht am 16. Dezember 2021
Gesehen am 10.01.2024